COMPARISON OF PHYTOREMEDIATION AZOLLA MICROPHYLLA AND PISTIA STRATIOTES AGAINST CADMIUM (CD) ABSORPTION IN NGIPIK LAKE - Nur Islakhun Nisa’; Elly Purwanti; Moh. Mirza Nuryady (Universitas Lambung Mangkurat, 2023)
Telaga Ngipik is water that is used by the community as a basic supply, and water supply to several industries. The content of heavy metal cadmium (Cd) in Ngipik lake can reduce water quality. The purpose of this study was to determine the phytoremediation ability of Azolla microphylla and Pistia stratiotes against the absorption of heavy metal Cd in Ngipik lake water samples. The method used in this study was a quasi-experimental method, with the independent variables being 5, 10, and 15 days of phytoremediation and types of aquatic plants. The research variables used were cadmium levels in the roots of aquatic plants. Sampling using random sampling. The sample used was 48 liters of Ngipik lake water for 4 replications. The results showed that Azolla microphylla was able to absorb the highest cadmium metal on day 15 with a level of 18.30 mg/kg, while Pistia stratiotes were able to absorb the highest cadmium metal on day 10 with a level of 11.28 mg/kg. Cadmium levels in water affect watercolor, water pH, and plant morphology. Following up on the findings in this study, it is suggested to use a wider variety of aquatic plants that have the potential to absorb Cd.